2016
DOI: 10.1111/tpj.13385
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome assembly and annotation of Glycyrrhiza uralensis, a medicinal legume

Abstract: SUMMARYChinese liquorice/licorice (Glycyrrhiza uralensis) is a leguminous plant species whose roots and rhizomes have been widely used as a herbal medicine and natural sweetener. Whole-genome sequencing is essential for gene discovery studies and molecular breeding in liquorice. Here, we report a draft assembly of the approximately 379-Mb whole-genome sequence of strain 308-19 of G. uralensis; this assembly contains 34 445 predicted protein-coding genes. Comparative analyses suggested well-conserved genomic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(111 citation statements)
references
References 69 publications
1
109
1
Order By: Relevance
“…A similar clade can be observed, including soybean GmSGT2 involved in transferring a galactosyl group from UDPgalactose to soyasapogenol B monoglucuronide (Shibuya et al, 2010) and five common bean candidates (Phvul.002G016400, Phvul.002G016500, Phvul.007G020600, Phvul.007G020700 and Phvul.007G020800). One common bean candidate (the candidate Phvul.010G101600) was identified in the cluster including MtUGT73K1, a UDP-glucosyltransferase shown to have specificity towards hederagenin and soyasapogenols B and E in Medicago (Achnine et al, 2005) and its putative counterpart in G. uralensis Glyur002597s00038050 (Mochida et al, 2017). Orthologs of these genes are only found in legumes, numbering between one and four copies in the species investigated ( Figure S7, UGT73K).…”
Section: Phylogenetic Analysis Of Candidate Genesmentioning
confidence: 99%
“…A similar clade can be observed, including soybean GmSGT2 involved in transferring a galactosyl group from UDPgalactose to soyasapogenol B monoglucuronide (Shibuya et al, 2010) and five common bean candidates (Phvul.002G016400, Phvul.002G016500, Phvul.007G020600, Phvul.007G020700 and Phvul.007G020800). One common bean candidate (the candidate Phvul.010G101600) was identified in the cluster including MtUGT73K1, a UDP-glucosyltransferase shown to have specificity towards hederagenin and soyasapogenols B and E in Medicago (Achnine et al, 2005) and its putative counterpart in G. uralensis Glyur002597s00038050 (Mochida et al, 2017). Orthologs of these genes are only found in legumes, numbering between one and four copies in the species investigated ( Figure S7, UGT73K).…”
Section: Phylogenetic Analysis Of Candidate Genesmentioning
confidence: 99%
“…Whole-genome sequencing has become a practical strategy to identify metabolic pathways for natural product biosynthesis (Liu et al, 2017;Mochida et al, 2017), and genome sequences of members of the order Lamiales such as Salvia miltiorrhiza (Zhang et al, 2015;Xu et al, 2016), Salvia splendens (Dong et al, 2018), and Sesamum indicum (Zhang et al, 2013) make feasible the comparative analysis to investigate how RSFs are produced in Scutellaria.…”
Section: Introductionmentioning
confidence: 99%
“…These findings, therefore, make the mining of genomic sequences for the identification of metabolic gene clusters a promising approach for the prediction and subsequent characterization of components of a biosynthetic pathway. Indeed, recent genomic sequences of important medicinal plants such as Catharanthus roseus (Kellner et al, 2015) and Glycyrrhiza uralensis (Mochida et al, 2017) have shown the existence of metabolic gene clusters, and further analysis may lead to new discoveries. Apart from metabolic gene clusters, genomics-facilitated genetic approaches for the discovery of metabolite pathways, including genome-wide association studies (GWAS) and expression quantitative trait loci (eQTLs), are important and have been successfully used in the model plant Arabidopsis and crops such as rice, maize and tomato among others (Brachi et al, 2011;Ingvarsson and Street, 2011;Pasam et al, 2012;Huang and Han, 2014).…”
Section: Sustainable Source Of Bio-active Metabolitesmentioning
confidence: 99%